2016
DOI: 10.1177/0363546516629949
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Injuries in Paralympic Track and Field Differs by Impairment and Event Discipline

Abstract: This is the first prospective cohort study examining injury IRs and associated factors in the sport of athletics at the Paralympic Games. Injury patterns were specific to the event discipline and athlete impairment. The majority of injuries occurred to the thigh (ambulant athletes) or shoulder/clavicle (wheelchair or seated athletes) and did not result in time loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 23 publications
3
35
0
1
Order By: Relevance
“…Three relevant studies [4][5][6] were located and categorized as shown in Table 1 (based on levels of evidence, Centre for Evidence-Based Medicine, 2011).…”
Section: Results Of Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Three relevant studies [4][5][6] were located and categorized as shown in Table 1 (based on levels of evidence, Centre for Evidence-Based Medicine, 2011).…”
Section: Results Of Searchmentioning
confidence: 99%
“…4,5 -Seated throwing field athletes had higher shoulder injury incident rate compared with wheelchair racing. 4 -The role that trunk control has on the risk of shoulder injury among wheelchair fencers may be an important consideration to mitigating injury. 5 -Sledge hockey and wheelchair curling reported a higher risk of upper-extremity injury compared with other winter parasports (eg, alpine skiing, Nordic skiing, biathlon).…”
Section: Summary Of Search Best Evidencementioning
confidence: 99%
See 3 more Smart Citations